2008
DOI: 10.1016/j.imlet.2008.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of T cells up-regulates expression of Ifi202, an interferon-inducible lupus susceptibility gene, through activation of JNK/c-Jun pathway

Abstract: Studies have revealed that increased expression of interferon (IFN)-inducible Ifi202 gene (encoding p202 protein) in splenic B and T cells from B6.Nba2 congenic (congenic for Nb2 locus derived from NZB mice) female mice is associated with lupus susceptibility. However, signaling pathways that regulate Ifi202 expression in immune cells remain to be elucidated. Here we report that stimulation of T cells up-regulates the Ifi202 expression. We found that steady-state levels of Ifi202 mRNA and protein were detectab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…Likewise, we recently noted [68] that stimulation of splenic T cells in vitro with anti-CD3 and anti-CD28 up-regulates the expression of the Ifi202 gene. Furthermore, generation of B6.Nba2 mice that were defective in type I IFN-signaling revealed that the defect resulted in only two fold reduction in Ifi202 mRNA levels in splenocytes as compared to the wild type mice [30].…”
Section: Regulation Of Ifi202 Expressionmentioning
confidence: 71%
“…Likewise, we recently noted [68] that stimulation of splenic T cells in vitro with anti-CD3 and anti-CD28 up-regulates the expression of the Ifi202 gene. Furthermore, generation of B6.Nba2 mice that were defective in type I IFN-signaling revealed that the defect resulted in only two fold reduction in Ifi202 mRNA levels in splenocytes as compared to the wild type mice [30].…”
Section: Regulation Of Ifi202 Expressionmentioning
confidence: 71%
“…Stimulation of splenic T cells from the NZB female mice by anti-CD3 and anti-CD28 up-regulates the expression of Ifi202 gene (Chen et al, 2008). Therefore, we investigated whether stimulation of splenic T or B cells regulates the expression of Aim2 gene.…”
Section: Resultsmentioning
confidence: 99%
“…Purified splenic T cells were stimulated as described previously (Chen et al 2008). In brief, freshly isolated splenic cells (2–4 ×10 6 ) were plated in 60 mm plastic cell culture plates either coated with purified hamster anti-mouse CD3 epsilon (10 μg/plate; from eBioscience, San Diego, CA) antibody or purified golden Syrian hamster IgG (5 μg/plate; from eBioscience) isotype control antibody.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11]30 In the present study, the number of T cells increased in female BXSB/MpJ glomeruli. Chen et al 31 demonstrated that the stimulation of both a mouse T-cell hybridoma cell line (2B4.11) and T cells derived from lupus-prone NZB upregulate the Ifi202b expression, in part, through the JNK/c-Jun pathway. On the basis of these findings, we proposed that the close correlation between renal overexpression of Ifi202b and infiltrating inflammatory cells exacerbates the pathological condition of MPGN in female BXSB/MpJ mice similar to other lupus-prone mice.…”
Section: Discussionmentioning
confidence: 99%